2020
DOI: 10.1055/s-0040-1716717
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Induced Cytokine Release Syndrome Associated with Pulmonary Vein Thromboses, Atrial Cardiomyopathy, and Arterial Intima Inflammation

Abstract: Coronavirus disease 2019 (COVID-19) is a viral disease induced by severe acute respiratory syndrome–coronavirus-2 (SARS-CoV-2), which may cause an acute respiratory distress syndrome (ARDS). First reports have shown that elevated levels of inflammatory cytokines might be involved in the development of organ dysfunction in COVID-19. Here, we can present a case of cytokine release syndrome induced by SARS–CoV-2 causing multiorgan failure and death. Of note, we can report on pulmonary vein thromboses as potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…These findings are consistent with histologic examinations of autoptic tissues from COVID-19 cases that confirmed high incidence of venous thromboembolisms ( Lodigiani et al, 2020 ), and microvascular thrombi with endothelial injury and swelling consistent with a thrombotic microangiopathy, in the lungs but also in the heart, liver, small bowel, kidney and other organs ( Goette et al, 2020 ; Varga et al, 2020 ; Pellegrini et al, 2021 ). Such complications have been observed also in pediatric population.…”
Section: Endothelial Dysfunction Coagulopathy Thrombotic Microangiopathy and Complement Activationsupporting
confidence: 85%
“…These findings are consistent with histologic examinations of autoptic tissues from COVID-19 cases that confirmed high incidence of venous thromboembolisms ( Lodigiani et al, 2020 ), and microvascular thrombi with endothelial injury and swelling consistent with a thrombotic microangiopathy, in the lungs but also in the heart, liver, small bowel, kidney and other organs ( Goette et al, 2020 ; Varga et al, 2020 ; Pellegrini et al, 2021 ). Such complications have been observed also in pediatric population.…”
Section: Endothelial Dysfunction Coagulopathy Thrombotic Microangiopathy and Complement Activationsupporting
confidence: 85%
“…Since macrophages are considered to be the main source of proinflammatory cytokines IL-1β, IL-6, IL-8, IFN-γ and TNF-α, these macrophage-secreted cytokines act on pulmonary vessel ECs, leading to their activation [ 165 ]. This has also been shown on COVID-19 lung autopsies, where alveolar macrophages expressing IL-6 and MCP-1 found in the lung tissues, leading to endothelial damage and necrosis that were evidenced by IL-6 secreting macrophages and ECs adhering to vascular thrombi [ 166 ]. Apart, neutrophils were also reported to drive the coagulatory cascade activation in COVID-19 patients.…”
Section: Sars-cov-2 and Its Receptors In Blood Vessel Pathophysiologymentioning
confidence: 64%
“…The evolution and characteristics of immune system activation are critical for determining the overall clinical outcomes of SARS-Cov-2 infection and other critical care illnesses, as well as the emergence of failure of specific organs (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). For example, it has been observed that lung function deteriorates by the direct cytotoxic effect of the virus and local inflammation governed by monocyte, T cells, and neutrophils during viral sepsis, including SARS-Cov-2 (6,(17)(18)(19). In another example, kidney function impairment in COVID-19 is triggered by vascular dysfunction and monocyte activation, which seemed to have distinct immune characteristics as compared to those seen in other organ failures (12,14,15,17).…”
mentioning
confidence: 99%